THE ROLE OF AROMA MARKETING IN THE FORMATION OF EMOTIONAL ATTACHMENT TO A BRAND (Marketing Journal, 2025)
The article explores aromamarketing as an effective tool of sensory influence that contributes to the formation of emotional attachment to a brand. Theoretical foundations of aromamarketing are discussed, and the impact of scents on consumer behavior and c ustomer loyalty is substantiated. Based on empirical analysis, the study identifies preferred scents for various business sectors and demonstrates their effect on brand perception.
Keywords: aromamarketing; emotional attachment; branding; sensory marketing; olfaction; scent; customer loyalty 604